The cruise of the Esquimaux, steam whaler, to Davis Straits and Baffin Bay, April-October 1899 - Walker, A. Barclay (Andrew Barclay), b. 1865. (Liverpool : Liverpool Printing and Stationery Co., 1900)
Mode of access: Internet.